Unbundling the influence of human capital on the new venture’s performance - Giones, Ferran (Animo Repository, 2019)
We use a longitudinal dataset on new ventures to assess the effects of human capital factors (education, work experience, and entrepreneurial experience) on new ventures’ performance. Our results show how the influence of human capital factors are dependent on the context (high vs. non-high technology industries) and illustrate the different effects of general and specific human capital factors. The findings help to clarify the existing debate on the influence of human capital where we introduce a longitudinal perspective that contributes to uncover the influence of factors such as prior experience, in particular if in the same industry, as a positive influence on new ventures’ future performance. © 2019 by De La Salle University.